2007
DOI: 10.1089/lap.2006.0054
|View full text |Cite
|
Sign up to set email alerts
|

Day-Case Laparoscopic Nissen Fundoplication in Children

Abstract: This paper is the first report in the pediatric literature to suggest that day-case laparoscopic fundoplication is feasible in children. Patients and caregivers find the procedure acceptable and it appears to be safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
8
0
3
Order By: Relevance
“…The first laparoscopic fundoplication on a child was performed in 1991 by Lobe [13]. Currently, it has a broad application in children and has even been performed on a day-case basis in some centres [14,15]. Our review establishes the fact that it is the most common MIS procedure in neonatal practice with an acceptably short operation time and low complication rate.…”
Section: Discussionmentioning
confidence: 67%
“…The first laparoscopic fundoplication on a child was performed in 1991 by Lobe [13]. Currently, it has a broad application in children and has even been performed on a day-case basis in some centres [14,15]. Our review establishes the fact that it is the most common MIS procedure in neonatal practice with an acceptably short operation time and low complication rate.…”
Section: Discussionmentioning
confidence: 67%
“…There were no randomized trials or meta-analyses included in the study. The studies identified were one prospective comparative study (comparing 22 outpatient surgeries to 16 inpatient surgeries, level 3b) [8], nine prospective noncomparative studies (level 4) [5,[9][10][11][12][13][14][15][16], and four retrospective noncomparative studies (level 4) [17][18][19][20] of which one involved children [20] and was analyzed separately. A literature review without data metaanalysis was published in 2005 and involved only seven published studies [21].…”
Section: Publications Identifiedmentioning
confidence: 99%
“…Only one study assessed the acceptability and safety of day-case laparoscopic fundoplication in children [20]. Twenty-one children were enrolled, with an average age of 4 years (range = 9 months to 11 years) and who experienced a surgical procedure (Nissen fundoplication) and perioperative management similar to those of adult patients.…”
Section: Ambulatory Laparoscopic Gastroesophageal Reflux Surgery In Pmentioning
confidence: 99%
“…As also indicated by previous studies, out-patient surgery is widely performed for many different types of pathologies in pediatric surgery centers but there seems to be a legitimate skepticism for the day-case approach in gastrointestinal surgery although reports of laparoscopic fundoplication and laparoscopic appendectomy on children in an out-patient setting were recently published (14,15). Doubtlessly, patient safety can not be jeopardized against all hospital costs, parental issues and surgeons' will, but we believe there is sufficient data in the literature showing that SDD for LC is safe and feasible for children as it is for adults with appropriate patient selection bias and management.…”
Section: Discussionmentioning
confidence: 95%